Without permission : conversations, letters, and memoirs of Henry Mandel - Flaks, Samuel, 1984- (Brookline, MA : Cherry Orchard Books, an imprint of Academic Studies Press, 2021)
"A fantastical propaganda play depicting an armed revolt financed the purchase of the yacht Abril and its conversion to an "illegal" immigrant passenger ship renamed the Ben Hecht. The plan was to evade the British naval blockade and bring Holocaust survivor refugees to Palestine. Henry Mandel volunteered aboard the Ben Hecht, a converted yacht that challenged the British blockade of Jewish immigrants to pre-state Israel. Captured and detained in Acre Prison, Mandel aided the efforts of prisoners planning an escape. After release, Mandel helped set up a secret bazooka shell plant in New York, which he helped to reassemble in Israel during the 1948 Arab-Israeli War. Mandel was an Orthodox Jew whose reminiscences provide a uniquely illuminating perspective on the creation of the Jewish state. Mandel's story is explicated in a running commentary that includes the personal narratives of other members of the Ben Hecht crew as well as historical background"--
Part One: Interviews and Reminiscences of Jewish Illegal Immigrant Ship Ben Hecht Crewman Henry Mandel -- Vienna Born, Bronx Bred -- The War Comes Home -- The Merchant Marine -- From Gowanus Canal to Atlantic Crossing -- Final Preparations -- The Irgun Had Other Ideas -- Bazooka Plant -- Part Two: Letters and Contextual Commentary -- The Bergson Group -- The Mission and the Crew -- Atlantic Crossing to the Mediterranean Sea -- The Palestine Run -- Piracy on the High Seas -- Breakout -- Release -- Machal -- A Mercy Ship's Legacy -- Part Three: Henry Mandel Reflects -- Family and Brotherly Love -- Civil Servant and Union Activist.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 31, 2021).
eBooks on EBSCOhost
Keywords: Mandel, Henry, -- 1920-2015 -- Interviews; Ben Hecht (Yacht) -- History; Bergson Group; Jewish refugees -- Palestine -- History -- 20th century; Zionists -- New York (State) -- New York -- Biography; Merchant mariners -- United States -- Biography; Palestine -- Emigration and immigration -- History -- 20th century; Réfugiés juifs -- Palestine -- Histoire -- 20e siècle.; Marins (Marine marchande) -- États-Unis -- Biographies; HISTORY / Jewish; Emigration and immigration; Jewish refugees; Merchant mariners; Zionists; Middle East -- Palestine; New York (State) -- New York; United States; 1900-1999; American Jewish history; Brooklyn Navy Yard; Jewish homeland; Orthodox Jew; Palestine; United States Merchant Marin; WWII; World War 2.; Zionism; merchant marines; refugees; Biographies; History; Interviews